Insulin signaling is acutely required for long-term memory in Drosophila - Chambers, Daniel B.; Androschuk, Alaura; Rosenfelt, Cory; Langer, Steven; Harding, Mark; Bolduc, Francois V. (Frontiers in Neural Circuits, 2015)
Memory formation has been shown recently to be dependent on energy status in Drosophila. A well-established energy sensor is the insulin signaling (InS) pathway. Previous studies in various animal models including human have revealed the role of insulin levels in short-term memory but its role in long-term memory remains less clear. We therefore investigated genetically the spatial and temporal role of InS using the olfactory learning and long-term memory model in Drosophila. We found that InS is involved in both learning and memory. InS in the mushroom body is required for learning and long-term memory whereas long-term memory specifically is impaired after InS signaling disruption in the ellipsoid body, where it regulates the level of p70s6k, a downstream target of InS and a marker of protein synthesis. Finally, we show also that InS is acutely required for long-term memory formation in adult flies.